A faster strongly polynomial time algorithm for submodular function minimization - Orlin, James B. (Mathematical programming, 2009)
We consider the problem of minimizing a submodular function f defined on a set V with n elements. We give a combinatorial algorithm that runs in O( n 5 EO  + n 6 ) time, where EO is the time to evaluate f ( S ) for some . This improves the previous best strongly polynomial running time by more than a factor of n . We also extend our result to ring families.